A study of basal crop coefficient for wheat under humid regime from heat unit accumulations - CHOWDHURY, A.; DAS, H.P.; GHUMARE, D. G. (MAUSAM, 1992)
A methodology has been presented to compute basal crop coefficient from soil moisture and heat unit accumulations, for wheat in the humid region of northeast India. In developing the method data from 1976-77 to 1981-82 crop seasons for the Sonalika variety of wheat from germination to maturity have been used and tested on independent data set for 1982-83 and 1985-86 crop seasons. Milk stage to physiological maturity stage is found to use maximum fraction of heat unit totals. The largest value of basal crop coefficient is about I 5 occurring during milk stage of the crop growth. Very high correlation is noticed between the actual ET and those computed from the model.